First Reprocessing of Southern Hemisphere Additional Ozonesondes (SHADOZ) Ozone Profiles (1998–2016): 2. Comparisons With Satellites and Ground‐Based Instruments. Issue 23 (4th December 2017) - Thompson, Anne M.; Witte, Jacquelyn C.; Sterling, Chance; Jordan, Allen; Johnson, Bryan J.; Oltmans, Samuel J.; Fujiwara, Masatomo; Vömel, Holger; Allaart, Marc; Piters, Ankie; Coetzee, Gert J. R.; Posny, Françoise; et al.
Abstract: The Southern Hemisphere ADditional OZonesonde (SHADOZ) network was assembled to validate a new generation of ozone‐monitoring satellites and to better characterize the vertical structure of tropical ozone in the troposphere and stratosphere. Beginning with nine stations in 1998, more than 7, 000 ozone and P ‐ T ‐ U profiles are available from 14 SHADOZ sites that have operated continuously for at least a decade. We analyze ozone profiles from the recently reprocessed SHADOZ data set that is based on adjustments for inconsistencies caused by varying ozonesonde instruments and operating techniques. First, sonde‐derived total ozone column amounts are compared to the overpasses from the Earth Probe/Total Ozone Mapping Spectrometer, Ozone Monitoring Instrument, and Ozone Mapping and Profiler Suite satellites that cover 1998–2016. Second, characteristics of the stratospheric and tropospheric columns are examined along with ozone structure in the tropical tropopause layer (TTL). We find that (1) relative to our earlier evaluations of SHADOZ data, in 2003, 2007, and 2012, sonde‐satellite total ozone column offsets at 12 stations are 2% or less, a significant improvement; (2) as in prior studies, the 10 tropical SHADOZ stations, defined as within ±19° latitude, display statistically uniform stratospheric column ozone, 229 ± 3.9 DU (Dobson units), and a tropospheric zonal wave‐one pattern with a 14 DU mean amplitude; (3) the TTL ozone column, which is also zonally uniform, masks complex vertical structure, and this argues against using satellites for lower stratospheric ozone trends; and (4) reprocessing has led to more uniform stratospheric column amounts across sites and reduced bias in stratospheric profiles. As a consequence, the uncertainty in total column ozone now averages 5%. Key Points: Data from 14 long‐term SHADOZ stations have been reprocessed according to best practices to correct for ozonesonde instrument variability Comparisons of total column ozone among reprocessed sonde data and satellite and ground‐based instruments agree within 2% for 12 of 14 stations In the tropics the 10‐station data bias among stratospheric ozone profiles has been markedly reduced and a tropospheric wave‐one remains